Peranan Gulf Cooperation Council terhadap Penyelesaian Konflik Qatar-Arab Saudi - Marzaman, Atika Puspita; Nasrun, Naswan; Darwis, Darwis; Abdullah, Nurjannah (State Islamic Institute of Kudus (IAIN Kudus), 2023)
This study aims to determine the role of the Gulf Cooperation Council (GCC) as a sub-regional organization in the Middle East region towards the settlement of the Qatar-Saudi Arabia conflict and the Qatar-Saudi Arabia conflict resolution strategy within the GCC Framework. The method used in this research is descriptive method with data collection techniques in the form of literature review sourced from books, journals, articles, official internet sites, and reports related to this research.The results of this study indicate that the GCC acts as an instrument for the Gulf countries to achieve their national goals. One of them is in the process of conflict resolution. The GCC acts as an arena where conflict resolution efforts between GCC member countries are mediated through the implementation of the 38th Summit to the 41st Summit. The Qatar-Saudi Arabia conflict resolution strategy within the GCC Framework was initiated by the GCC member countries, namely Kuwait and Oman. The two countries continue to maintain good relations with Qatar and resolve GCC internal disputes by establishing mediation between Qatar and Arab countries.